Fisher, Bayes, and Predictive Inference - Sandy Zabell (Mathematics, 2022)
We review historically the position of Sir R.A. Fisher towards Bayesian inference and, particularly, the classical Bayes–Laplace paradigm. We focus on his Fiducial Argument.